Influence of a Medium-Impact Exercise Program on Health-Related Quality of Life and Cardiorespiratory Fitness in Females with Subclinical Hypothyroidism: An Open-Label Pilot Study. (12th January 2014) - Garces-Arteaga, Andrea; Nieto-Garcia, Nataly; Suarez-Sanchez, Freddy; Triana-Reina, Héctor Reynaldo; Ramírez-Vélez, Robinson
Abstract : Objective. To examine the influence of a medium-impact exercise program (MIEP) on health-related quality of life (HRQoL) and cardiorespiratory fitness (VO 2 max ) in females with subclinical hypothyroidism (sHT). Materials and Methods. We selected 17 sedentary women with sHT (mean age: 43.1 (standard deviation: 9.7) years). Participants carried out an MIEP consisting of 3 weekly sessions of 60 minutes during 12 weeks. Before and after the exercise program HRQoL was assessed by the SF-12v2 questionnaire, and VO 2 max was evaluated by Rockport walk test. Results. After the 12-week intervention, the participants that performed an MIEP showed improvements in HRQoL in most domains, particularly the vitality domain by 7 points, the social functioning domain by 10 points, the mental health domain by 7 points, and the mental component summary by 7 points. One of the four domains within the physical component summary (general health domain) showed significant effect of the exercise intervention: 6 points. Moreover, the participants that performed exercise showed a higher VO 2 max (28%; P < 0.01 ). Conclusion. After 12 weeks of medium-impact exercise program, there were remarkable improvements in HRQoL in most domains. Moreover, this exercise program proved to have a positive influence on cardiorespiratory fitness.